Short-term lifestyle education on obesity reduction in adolescents - Ning, Feng; Sun, Xiaohui; Ge, Bing; Li, Shunping; Hou, Binghui; Wang, Yumei; Zhang, Dong (Frontiers in Medicine, 2024)
Backgrounds: Obesity is increasing in adolescents in China. However, the awareness of obesity and prevention on related risk factors were not well known. We aim to assess the effectiveness of short-term health education intervention on obesity in Chinese adolescents. Methods: In this study, 42 primary and secondary schools from Qingdao were randomly divided into the education and control groups. A total of 11,739 adolescents was included in the current study. The logistic regression was employed to assess odds ratio (OR) of education intervention on overweight and obesity prevalence adjusting for covariates. Results: The baseline prevalence of overweight and obesity was significantly higher in urban than in rural areas and in boys than in girls. After one year lifestyle intervention, the proportion of students with awareness of obesity was higher, meanwhile age-adjusted mean values of weight, body mass index, duration of watching TV and doing homework were lower in education group than control group. The corresponding figures were 43.6(95%CI [confidence intervals]; 43.3–43.9)kg versus 44.3(95%CI; 44.0–44.6)kg, 18.6(95%CI; 18.5–18.7)kg/m2 versus 18.9(95%CI; 18.8–19.1)kg/m2, 1.3(95%CI; 1.2–1.3)hours/d versus 1.4(95%CI; 1.3–1.4)hours/d, and 1.5(95%CI; 1.4–1.5)hours/d versus 1.8(95%CI; 1.7–1.8)hours/d. The multivariable adjusted OR for combined prevalence of overweight and obesity was 0.85(95%CI; 0.76–0.96) in education group as compared with control group. Conclusions: Short-term health education intervention results in significantly higher reductions in obesity parameters and improvement in awareness in Chinese adolescents.